Julius Caesar - Shakespeare, William, 1564-1616 (Stage Door, 2014)
William Shakespeare was born in Stratford-upon-Avon in late April 1565 and baptised there on 26th April. He was one of eight children. Little is known about his life but what is evident is the enormous contribution he has made to world literature. His writing was progressive, magnificent in scope and breathtaking in execution. His plays and sonnets helped enable the English language to speak with a voice unmatched by any other. William Shakespeare died on April 23rd 1616, survived by his wife and two daughters. He was buried two days after his death in the chancel of the Holy Trinity Church. The epitaph on the slab which covers his grave includes the following passage, Good friend, for Jesus's sake forbear, To dig the dust enclosed here. Blessed me the man that spares these stones, And cursed be he that moves my bones. Here we publish his tragedy from 1599 'Julius Caesar'.